Verbascoside Protects Mice From Clostridial Gas Gangrene by Inhibiting the Activity of Alpha Toxin and Perfringolysin O - Zhang, Jian; Liu, Shui; Xia, Lining; Wen, Zhongmei; Hu, Naiyu; Wang, Tingting; Deng, Xuming; He, Jiakang; Wang, Jianfeng (Frontiers in Microbiology, 2020)
Gas gangrene, mainly caused by the anaerobic bacterium Clostridium perfringens (C. perfringens), causes death within 48 h of onset with limited therapeutic strategies and extremely high mortality. Both C. perfringens alpha toxin (CPA) and perfringolysin O (PFO) are important virulence factors in the development of gas gangrene, suggesting that these toxins are the targets to fight this infection. Here, we found that verbascoside, a phenylpropanoid glycoside widely distributed in Chinese herbal medicines, could effectively inhibit the biological activity of both CPA and PFO in hemolysis assays. The oligomerization of PFO was remarkably inhibited by verbascoside. Although no antibacterial activity was observed, verbascoside treatment protected Caco-2 cells from damage caused by CPA and PFO. Additionally, infected mice treated with verbascoside showed significantly alleviated damage, reduced bacterial burden and decreased mortality. In summary, verbascoside treatment produces an effective therapeutic effect against C. perfringens virulence both in vitro and in vivo by simultaneously targeting CPA and PFO. Our results provide a promising strategy and potential lead compound for C. perfringens infections, especially gas gangrene.